ANALYSIS OF FISCAL CAPACITY ON HUMAN DEVELOPMENT INDEX WITH MANDATORY SPENDING ON EDUCATION AND HEALTH AS INTERVENING VARIABLE (AN EMPIRICAL STUDY ON REGENCIES/CITIES IN JAVA) - Bawono, Andy Dwi Bayu; Purbasari, Heppy; Mujiyati, Mujiyati (Muhammadiyah University Press, 2018)
Regional autonomy is aimed at enhancing the proximity between the local government and its people, in terms the local government will identify the weaknesses and strengths of its area from the highest to lowest level. This research attempts to find out the influence of the Fiscal Capacity Index on the Human Development Index with mandatory spending on education and health as the intervening variables. The research used empirical and explanatory research method to analyze the fiscal capacity index on the intervening variables. This study involved secondary data, which were obtained from certain agencies, namely the Regulation of Minister of Finance (PMK No.119/PMK.07/2017), the GRDP Realization Report of Regencies/Cities in Java Fiscal Year 2016, and the data published by the Central Bureau of Statistics of Regencies/Cities in Java in 2017. The results of the hypothesis analysis reveal that the fluctuation in the Fiscal Capacity Index in each region is able to influence the amount of mandatory spending in education and health. Meanwhile, the Path Analysis test indicates that the Fiscal Capacity Index has a stronger influence on the Human Development Index without any intervention from mandatory spending on education and health. Essentially, the Fiscal Capacity Index is the main variable that affects the Human Development Index.